Depth of poverty in an informal settlement in the Vaal region, South Africa - Wilna Oldewage-Theron; Tielman J.C. Slabbert (AOSIS, 2010)
Despite the large number of people currently living in poverty in sub-Saharan Africa, the debate about the definition and meaning of poverty continues. Two distinct problems exist regarding the measurement of poverty, namely the difficulty of identifying the poor in a population and the difficulty in developing an index for the measurement of poverty. The main objective of the survey was to apply a poverty model for determining the depth of poverty in an informal settlement in the Vaal Region, as well as the impact of possible income-generating activities on the community. A questionnaire, which had been devised for measuring poverty indicators, was administered to 429 randomly selected households in the informal settlement, with the poverty model being applied to measure the degree of poverty. The results of the survey showed that 286 households lived in poverty at the time. The impact of extra income on the poverty levels of these 286 households was then determined. The results of the survey also showed that the unemployment level was 91% and that the mean monthly income was R612.50. The average poverty gap was R1017.21, with the poverty gap ratio being 56%. The poverty model showed that an increase of R500 in monthly household income resulted in a poverty gap ratio of 35%. The results indicated that the community was a poverty-stricken community, suffering from chronic food insecurity. The results of the study will be used to facilitate the planning and implementation of sustainable, income-generating, community-based interventions aimed at promoting urban food security and alleviating poverty in the community in question. Opsomming Ten spyte van die groot hoeveelheid mense wat steeds wêrelwyd in armoede leef, duur die debat oor die definisie en betekenis van armoede nog altyd voort. Daar word twee definitiewe probleme met die meting van armoede ervaar, naamlik die identifisering van die armes in 'n gemeenskap, en die ontwikkeling van 'n indeks vir die meet van armoede. Die hoofdoel van hierdie studie was om 'n armoedemodel vir die dieptemeting van armoede in 'n informele nedersetting in die Vaal-area toe te pas, en om die impak van moontlike aktiwiteite wat inkomste genereer in dieselfde gemeenskap te bepaal. 'n Vraelys wat ontwerp is om armoede aan te dui en te meet is ewekansig aan 429 huishoudings in die informele nedersetting uitgedeel om te voltooi en die armoedemodel is toegepas om die diepte van armoede te meet. Die resultate het getoon dat 286 huishoudings in armoede leef. Die impak van ekstra inkomste op armoedevlakke is in die 286 huishoudings bepaal. Die resultate het verder getoon dat die werkloosheidsvlak 91% was en dat die gemiddelde maandelikse huishoudelike inkomste R612.50 was. Die gemiddelde armoedegaping was R1017.21, met 'n armoedegapingverhouding van 56%. Die armoedemodel het getoon dat 'n verhoging van R500 in maandelikse huishoudelike inkomste die armoedegapingverhouding na 35% verlaag het. Die resultate het bewys dat hierdie 'n armoedige gemeenskap met kroniese voedselonsekerheid was. Die uitkoms van die studie sal gebruik word vir die beplanning en implementering van gemeenskapgebaseerde ingrypings om volhoubare inkomste te genereer om stedelike voedselsekerheid te bevorder en die armoede in hierdie gemeenskap te verlig.